The Association between Shirodkar Cerclage and Preterm Premature Rupture of Membranes in Singleton Pregnancies - Muniz Rodriguez, Alberto; Pastor, Andrew; Fox, Nathan S. (American Journal of Perinatology, 2020)
Objective The aim of this study was to estimate if preterm premature rupture of membranes in women with cerclage is due to the cerclage itself or rather the underlying risk factors for preterm birth in this population.Study Design This was a retrospective cohort study of singleton pregnancies who underwent Shirodkar cerclage by a single maternal–fetal medicine practice between 2005 and 2019. The control group was an equal number of randomly selected women with a singleton gestation who had a prior preterm birth and were treated with 17-OH-progesterone but no cerclage. Patients with major uterine anomalies or fetal anomalies were excluded. The primary outcome was preterm premature rupture of membranes prior to 34 weeks. Chi-square and logistic regression were used.Results A total of 350 women with cerclage (154 [44%] history-indicated, 137 [39%] ultrasound-indicated, and 59 [17%] exam-indicated) and 350 controls were included. Preterm premature rupture of membranes prior to 34 weeks did not differ between the groups (8.9% in cerclage vs. 6.0% in controls, p = 0.149, adjusted odds ratio 0.62, 95% confidence interval: 0.24–1.64) nor between the different cerclage indications (9.1% of history-indicated, 7.3% of ultrasound-indicated, and 11.9% of exam-indicated, p = 0.582). This study had 80% power with an α error of 0.05 to detect an increase in preterm premature rupture of membranes prior to 34 weeks from 6.0% in the control group to 12.0% in the cerclage group.Conclusion Cerclage does not increase the risk of preterm premature rupture of membranes prior to 34 weeks compared with other women at increased risk of preterm birth. The observed association between cerclage and preterm premature rupture of membranes is likely due to underlying risk factors and not the cerclage itself. The risk of preterm premature rupture of membranes prior to 34 weeks in women with cerclage is 10% or less and does not appear to differ based on cerclage indication.Key Points
Keywords: cerclage; preterm premature rupture of membrane; premature rupture of membranes; preterm birth